Induction of DNA polymerase in polyoma virus-infected mouse cells requires transcription and translation. - Wintersberger, E (1976)
The induction of DNA polymerase activity and of DNA synthesis in polyoma virus-infected mouse kidney cells is inhibited by actinomycin D and cycloheximide, even in cells that are already T-antigen positive. This indicates that the induction of the DNA-synthesizing apparatus requires transcription and translation. The increase in cellular DNA polymerase activity and in the DNA synthesizing capacity follows the appearance of T-antigen only after a characteristic lag period of several hours.